Developmental profile of Filipino children born during the SARS-COV-2 pandemic: pilot study - Dy, Angel Belle C.; Edillon, Michelle Alexandra; Malonzo, Mikhaela Francesca Marietta A.; Garcia, Glenda Darlene; Dy, Alane Blythe C.; Espiritu, Clarisse Joyce S.; Aquino, Ma. Bianca Carmela; So, Shannen Louise T.; Capulong, Nina Linly D.; Dagal, Rizza Victoria C.; Sumpaico Tanchanco, Lourdes Bernadette (Frontiers in Public Health, 2024)
Objective The Philippines experienced one of the longest restriction periods during the COVID-19 pandemic. This study aimed to provide a developmental profile of 18–25 month-old children and identify factors associated with their development during their early years being born and raised during the pandemic. Methods The study population was recruited through convenience sampling among families living in proximity to the daycare centers in Cainta, Rizal, Philippines. 116 children qualified to participate and underwent developmental screening using the Early Childhood Care and Development (ECCD) Checklist and their parents were interviewed related to demographic and social factors. Results The mean score of the children’s Overall Development is 106.47 (SD = 13.43) indicating that children’s skills were within the expected range of 80–119. Girls had significantly higher mean scores compared to boys [MGirl = 111.23, SDGirl = 9.95 vs. MBoy = 101.18, SDBoy = 14.83 t(114) = −4.32 p < 0.001]. Mean scores were highest among children whose mothers completed a high school education (MHigh School = 107.76, SDHighSchool = 12.47) compared to those who have some or have completed an elementary education (MSomeElem = 72.50, SDSomeElem = 6.36 and MElem = 103.58, SDElem = 13.86 respectively) [F(2, 113) = 8.18, p < 0.001]. Unadjusted linear regression shows a modest increase in mean scores as the number of household members increased [ꞵ = 0.86, (CI: 0.02, 1.70), t-score (1, 113) = 2.03, p = 0.045]. Conclusion The developmental skills of 18–25 month-old children born and raised during the COVID-19 pandemic in an urban municipality in the Philippines are within average scores. Both hindering and protective demographic factors were identified as associated with the children’s developmental evaluation scores. It is important to acknowledge these factors and continue monitoring the children’s development and address needs among children who may need further support.